2003
DOI: 10.1016/s1074-5521(03)00046-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bacterial Virulence

Abstract: Agents that target bacterial virulence without detrimental effect on bacterial growth are useful chemical probes for studies of virulence and potential candidates for drug development. Several gram-negative pathogens employ type III secretion to evade the innate immune response of the host. Screening of a chemical library with a luciferase reporter gene assay in viable Yersinia pseudotuberculosis furnished several compounds that inhibit the reporter gene signal expressed from the yopE promoter and effector pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(111 citation statements)
references
References 33 publications
0
110
0
Order By: Relevance
“…A class of acylated hydrazones was recently identified that inhibited TTS of Y. pseudotuberculosis without affecting the in vitro growth rate (2,3). The same class of compounds has also been shown to inhibit TTS of Pseudomonas aeruginosa as well as S. typhimurium (unpublished data), suggesting that these compounds target the secretory apparatus itself rather than individual effector molecules.…”
Section: Discussionmentioning
confidence: 95%
“…A class of acylated hydrazones was recently identified that inhibited TTS of Y. pseudotuberculosis without affecting the in vitro growth rate (2,3). The same class of compounds has also been shown to inhibit TTS of Pseudomonas aeruginosa as well as S. typhimurium (unpublished data), suggesting that these compounds target the secretory apparatus itself rather than individual effector molecules.…”
Section: Discussionmentioning
confidence: 95%
“…In summary, small-molecule screening provides a powerful approach to studying invasion and other experimentally challenging questions in host-pathogen interaction (2,34,35). At the same time, the approach may generate small-molecule probes that will prove useful in other experimental systems, and it may identify protein-small molecule pairs of relevance to antimicrobial drug development.…”
Section: )mentioning
confidence: 99%
“…A primary assay utilizing the bacterial clone Y. pseudotuberculosis YPIII(pIB102-Elux), 15 with a luminescent reporter gene under the control of the promoter for the T3SS effector protein YopE, detected three library fractions derived from both leaf extracts of two Papua New Guinean Anisoptera (Dipterocarpaceae) species, A. thurifera and A. polyandra, that inhibited the luminescent signal. To verify the positive hits a colorimetric assay to detect the protein tyrosine phosphatase enzyme activity of the secreted effector protein YopH was performed in conjunction with a standard antibacterial growth assay, 41 and suggested that these fractions selectively inhibited the T3SS.…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2+ depletion at 37 °C stimulates Yop production and the Yop production will eventually suppresses growth. 15 Fractions were tested at single point concentrations of 7.14 μge/μL Active fractions and controls were retested at 7.14, 1.42, 0.71, 0.14 and 0.071 μge/μL. Pure compounds were screened at 10, 20, 50 and 100 μM.…”
Section: Acid Hydrolysis Ofmentioning
confidence: 99%
See 1 more Smart Citation